Betasianin Analysis of Dragon Fruit (Hyolecerus polyrhizus) West Sumatra as A Natural Colorant - Putri, Amaliani; Yuniarti, Elsa; Violita, Violita; Chatri, Moralita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The growing demand for natural food colorants, driven by consumer awareness of the health risks associated with synthetic additives, has increased the exploration of plant-based pigments. Betacyanin, a red-violet pigment in the betalain group, has drawn attention for its color stability and antioxidant properties. This study aimed to analyze the betacyanin content in the peel of red dragon fruit (Hylocereus polyrhizus) from two cultivation areas in West Sumatra (Tanah Datar and Bukittinggi) as a potential natural food colorant. The dragon fruit peels were dried, ground into powder, and extracted using 10% citric acid solution. The extract was concentrated and analyzed using UV-Vis spectrophotometry. Results showed a significant difference in betacyanin levels between the two sources: Tanah Datar samples had an average of 28.48±0.19 mg/100g, while Bukittinggi samples had 3.52±0.07 mg/100g. These findings suggest that geographical and environmental factors significantly affect pigment accumulation. It is recommended that Tanah Datar dragon fruit peel be further developed as a natural colorant due to its high betacyanin content, supporting sustainable practices and waste reduction in food processing.